Internalization of Religious Values in Early Childhood - Ni Luh Drajati Ekaningtyas; I Made Ardika Yasa (CV. Syntax Corporation Indonesia, 2022)
Internalization of religious values is one of the efforts that can be made to build the next generation of the nation who is not only intelligent but also has a noble character. This study aims to analyze the strategies applied by teachers in an effort to internalize religious values in early childhood. This research is a descriptive qualitative research. Data was collected by using interview, observation, and documentation techniques. Respondents in this study consisted of principals, teachers, and representatives of parents of early childhood. The internalization strategy is applied by telling stories, singing, doing yoga, praying, visiting places of worship or religious tourism, setting an example, and habituation through routine activities. The strategies implemented have succeeded in facilitating the religious development which can be seen from children who have been able to know their religion and God, are accustomed to praying and worship according to their religion, understand noble behavior, distinguish good and bad behavior, recognize rituals and religious holidays, as well as respecting the religions of others.